Student Management in Tahfidz Extracurriculars - Nuzleha; Neni Septiana; Afiful Ikhwan; Wihdatus Syifa Anwar (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2023)
This study aims to describe students' planning system and implementation management in developing their talents in memorization with extracurricular tahfidz at the Integrated Muhammadiyah Elementary School (SDMT) Ponorogo, East Java. The research method used was qualitative, with a case study design and data collection techniques through interviews, observation, and documentation. The main objects in this study were informants from the tahfidz extracurricular coordinator and samples from the tahfidz extracurricular students themselves. This research resulted in: (1) Management planning of students in the extracurricular tahfidz at the integrated Muhammadiyah Elementary School in Ponorogo using the halaqah system, forming an ad hoc team consisting of the coordinator-secretary-teacher halaqah-infrastructure, only those who have passed iqra' are allowed to participate in extra tahfidz evidenced by a certificate of completion). (2) Implementation of student management in the tahfidz extracurricular at the integrated Muhammadiyah Elementary School in Ponorogo: tahfidz extracurricular activities after the core class hours are over, namely at 14.30-16.00 WIB every thursday & friday, using the nahawan tone, each student is recorded and uploaded on LP3Q youtube for archives and general learning evaluation materials, the method used is talkin & sorogan, a tasmi' exam is held for special follow-up evaluation.